Spatial Zoning of Tourism Carrying Capacity Using GIS in Darma Reservoir Ecotourism - Hafiz Fauzan Fetra; Purnomo Adi Saputro (Universitas Negeri Gorontalo, 2026)
Tourism carrying capacity (TCC) assessment is essential for balancing tourism development and environmental sustainability, particularly in ecotourism destinations experiencing fluctuating visitor demand. This study aimed to determine the physical carrying capacity (PCC), real carrying capacity (RCC), and effective carrying capacity (ECC) of Darma Reservoir Ecotourism in Kuningan Regency, Indonesia, using a zone-based geographic information system (GIS) approach. The analysis integrated high-resolution spatial data, including data from the National Aeronautics and Space Administration Global Precipitation Measurement (GPM) on rainfall and the National Digital Elevation Model System (DEMNAS), to derive environmental correction factors for RCC calculations. PCC was calculated based on tourism area, recreational space requirements, and visitor rotation factors, whereas ECC incorporated management capacity through staff and facility adequacy assessments. The results showed that the overall land-based tourism area had a PCC of 3,123 visitors/day, which decreased to 1,955 visitors/day after environmental corrections and further declined to an ECC of 1,787 visitors/day after considering management capacity. Zone-specific ECC values were 37 visitors/day for Picnic 1, 215 visitors/day for Picnic 2, 30 visitors/day for the Camping Ground, and 883 boat trips/day for the Boat Tour zone. A comparison with actual visitation revealed that weekday and weekend visitor numbers remained below the ECC threshold, whereas peak-season visitation during Eid al-Fitr and New Year holidays substantially exceeded the carrying capacity. These findings indicate the need for adaptive tourism management, including visitor quotas and reservation systems during peak periods, alongside promotional and diversification strategies during the low season. The study demonstrates that integrating GIS-based spatial analysis with carrying-capacity assessment provides an effective framework for sustainable ecotourism management.